Multiproxy analyses of paleoenvironmental and paleoceanographic changes during the Danian-Selandian in East Central Sinai: An integrated stable isotope and planktic foraminiferal data - Farouk, Sherif; Jain, Sreepat; Ahmad, Fayez; Abu-Alam, Tamer; Al-Kahtany, Khaled; El Agroudy, Ibrahim S.; Bazeen, Youssef S.; Shaker, Fatma (Frontiers in Earth Science, 2023)
Forty-three planktic foraminifera samples from the Themed section (East Central Sinai; Egypt) spanning the Zone Parvularugoglobigerina eugubina (Pα) to the Subzone Acarinina subsphaerica (P4b) have been studied. Data from δ13C, δ18O, and planktic foraminifera-based species diversity, depth habitat, preference for warm and cool surface waters, and nutrients (oligotrophic, mesotrophic, and eutrophic conditions) are used to infer paleoenvironmental changes throughout the Danian‒Selandian duration. Based on quantitative multivariate analyses (hierarchical cluster and principal component), three distinct intervals were recognized, Interval 1 (Pα‒P1b), Interval 2 (P1c‒P3a), and Interval 3 (P3a‒P4b). Interval 2 is further subdivided into three subintervals, 2a (part P1c), 2b (part P1c), and 2c (P2‒P3a). Two δ13C events are identified, Dan‐C2 and Latest Danian Event (LDE) and elaborated concerning paleoenvironmental changes. During the earliest Danian planktic foraminiferal Pα Zone, moderately shallow and eutrophic conditions prevailed with cool surface waters and a shallow thermocline. Comparable conditions were still prevailing during P1a‒P1b, but with slightly deeper and mesotrophic conditions and a somewhat deeper thermocline and reduced stratification. P1b‒P1c exhibits a major shift from Eoglobigerina to Subbotina‒Parasubbotina with cooler surface waters and moderate mesotrophic conditions. For Subzone P1c (upper part), slightly mesotrophic conditions were inferred, whereas for P2‒P3a (lower part), surface water warming and thermocline shallowing events have inferred with increased oligotrophic conditions. The Latest Danian Event (mid-P3a) is marked by a dramatic negative δ13C excursion, warm waters, increased mesotrophic conditions, and enhanced stratification. The dominance of Morozovella, Acarinina, and Igorina specify warm and oligotrophic conditions for subzones P3b‒P4b.